Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Keputusan Pembelian pada PT. Batam Bangun Prathama - Agustina Agustina; Triana Ananda Rustam (Ekonomis: Journal of Economics and Business, 2023)
This very valuable company asset has a vital function in increasing the quality of service and the quality of agency work in maintaining consumer loyalty to keep shopping at the company. This study aims to understand the impact of product quality and service quality on purchasing decisions. The type of study used is quantitative through the use of Lemeshow sampling technique. The application used to help process the data in this research is SPSS version 25, while the sample in this study is 384 respondents. To collect data carried out by distributing questionnaires. The results of statistical tests can be determined if the variables of product quality, service quality, and purchasing decisions are normally distributed, in which the independent variables in this study show no signs of multicollinearity and heteroscedasticity. The results of the t test show that the product quality and service quality variables have a good and significant impact on purchasing decisions, and the f test results show that the product and service quality variables have a simultaneous impact on purchasing decisions.